تأثير التعديل المتكيف على معدل الإرسال في شبكات الاتصال النقالة - الرضوان هيثم (Latakia University Journal -Engineering Sciences Series, 2017)
يهدف البحث إلى تحليل أداء النظام الخليوي من خلال دراسة تأثير تقنية التعديل المتكيف على معدل الإرسال. استخدمت في الدراسة تقنية المنطق العائم لتحليل معدل الإرسال للوصلة الهابطة اعتماداً على كل من نوع التعديل المستخدم وجودة التغطية والمسافة بين المرسل والمستقبل. حيث تمت معالجة أربعة بارامترات لمتحولات الدخل في نظام المنطق العائم وهي : استطاعة المحطة و جودة التغطية ونمط التعديل المستخدم و نسبة الإشارة إلى الضجيج ، بينما اعتمد بارامتر واحد للخرج وهو فعالية الطيف المستخدم ممثلاً بمعدل الإرسال بالبت في الثانية لكل هرتز. كما تم تقديم دراسة تحليلية لتحديد القيم المثلى لبارامترات الأداء الرئيسية المعتمدة لتحديد أفضل معدلات الإرسال من أجل قيم تعديل مختلفة بالإضافة إلى دراسة توابع العضوية لكل من محددات الدخل والخرج للبارامترات المؤثرة على معدل الإرسال باستخدام تقنية المنطق العائم. This works aims to study the performance of the mobile system via studying the effects of adaptive modulation technique on the data rate. Fuzzy logic technique is used as a tool to analyze the data rate of the downlink connection depending on type of modulation, coverage quality and the distant between the receiver and the transmitter. For parameters were considered as input parameters for the fuzzy logic system mainly are: power of the station, quality of coverage, the type of modulation technique and the signal to interface noise ratio. One parameter is used as an output of the fuzzy system which is spectrum efficiency in bit per second per hertz. Analytical study to select the optimal data rates for different modulation techniques will be considered. Additionally, studying the input and output memberships of the data rate parameters using fuzzy logic will be explained. Keywords: Data rate, downlink, signal to noise ratio, modulation type, Fuzzy logic, spectrum efficiency.